A novel subspecies-specific primer targeting the gyrase B gene for the detection of Pectobacterium carotovorum subsp. brasiliense - Tri Joko; ALAN SOFFAN; MUHAMMAD SAIFUR ROHMAN (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Joko T, Soffan A, Muhammad Saifur Rohman MS. 2019. A novel subspecies-specific primer targeting the gyrase B gene for the detection of Pectobacterium carotovorum subsp. brasiliense. Biodiversitas 20: 3042-3048. Pectobacterium carotovorum subsp. brasiliense is one of the major causative bacterial pathogens of the soft rot disease in various crops. It has a high virulence and a wide range of hosts in the tropics and the subtropics. Most often, conventional methods are not able to accurately distinguish P. carotovorum subsp. brasiliense from other subspecies. Thus, this study aimed to design a specific gyrase B gene (gyrB) -based primers for the detection and identification of soft rot pathogen. The specific primers design was based on the alignment using gyrB gene sequence data from P. carotovorum subsp. brasiliense and other data from the GenBank. The primers comprised of F-gyr-Pcb (5’-CAC AGG CAC CGC TGG CTG TT-3’) and R-gyr-Pcb (5’-CGT CGT TCC ACT GCA ATG CCA-3’) with an amplicon of 336 base pairs. The specificity of the primers pair was verified both in silico and in polymerase chain reaction (PCR) assays, where the primers could only detect P. carotovorum subsp. brasiliense. Primers’ sensitivity was determined by qualitative PCR with a detection limit of less than 0.5 ng/µL of genomic DNA. Hence, the proposed detection tool can be beneficial to advance further studies on the ecology and epidemiology of soft rot diseases.